Elizabeth of East Hampton : a novel - Bellezza, Audrey; Harding, Emily (For the love of Austen, 2024)
"A modern retelling of Jane Austen's Pride and Prejudice that transports you to summer in the Hamptons, where classes clash, rumors run wild, and love has a frustrating habit of popping up where you least expect it"--